The impact of digital storytelling on motivation and achievement in teaching scientific concepts for Kindergarten children - Al-Jabriya, Najma Nasser (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to measure the impact that storytelling has on motivation and achievement in teaching scientific concepts for the kindergarten children. An experimental design was used to achieve such aim, it was implemented on a sample of 40 children (KG2 in specific). The children were randomly divided into two groups of 20 (control and experimental). The researcher designed the digital story narration in the experimental treatment stage after selecting one of the scientific concepts from the National curriculum for the pre study stage.The results revealed that there is a difference in academic achievement between the pre and post-test for the benefit of the experimental group, and this indicates the effective effect of using the digital storytelling in teaching the scientific concepts of this stage. The motivation scale was also applied to the research sample, which resulted in a high level of motivation to learn scientific concepts after using digital storytelling.This indicates the effectiveness of this method to attract children's attention and increase their focus and motivation. And give meaning to these scientific concepts.
Keywords: Digital storytelling; Motivation; scientific concepts; pre school